A Study on the Sustainable Architecture Principles and Solutions to Implement It - Niknam, Mehdi (Mathematical Statistician and Engineering Applications, 2023)
Humans seek to create a space where they can find the best solution to fulfill their needs by understanding peace, security, and sense of belonging. In this chain, nature is the integral element and it is the law governing the human life, and this thought has been highly embodied in the Iranian traditional architecture and such great architects as Frank Lloyd Wright has highly considered the relation between architecture and nature. Architecture remains sustainable when it is parallel with the nature not perpendicular to it. Nature is a law with fixed values. A stage must be provided that the humans can continue their efforts for survival in a pure environment because without global environmental security, national and even social security cannot be guaranteed. Respect for the environment and nature and having knowledge about ecology, topography, and climatic conditions are required. So, sustainable design is not a formal style and does not stem from momentary impulses; rather it implies deep concepts that link human, nature, and architecture. By enjoying theoretical findings of sustainable architecture and rich architectural traditions and local urbanization simultaneously, we can step towards improving environmental sustainability instead of uncontrolled expansion of low density cities